Maternal and perinatal outcome of pregnancy in women with one previous caesarean section-a study at a tertiary care centre - Venkatesh, Deepthi; Huilgol, Varun G.; Huilgol, Gopalkrishna B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Increasing rates of primary caesarean section has led to an increased proportion of obstetric population with history of prior caesarean delivery. There is growing concern by obstetrician for optimizing the management of these high risk cases. The present study was undertaken to evaluate obstetric and fetal outcome of patients presenting at term with history of one previous LSCS. Methods: This was a prospective hospital based observational study conducted at Vani Vilas Hospital and Bowring and Lady Curzon Hospital, Department of OBG, BMC and RI, Bangalore. The study included 300 patients who had undergone previous one LSCS with term pregnancy. Results: Majority of patients, that is 186 (62%) were in the age group of 21 to 25 years. Out of 300 patients, 94 (31.33%) patients went for repeat LSCS without trial. 206 (68.67%) patients were included in the trial of labour group, out of which 109 (52.9%) patients had successful vaginal delivery. 97 (47.1%) patients went for repeat LSCS in trial group due to various indications, commonest being scar tenderness. Conclusions: Delivery of patients with previous caesarean section should always be conducted in a well-equipped hospital where facilities for immediate intervention are available if necessity arises. These patients should be counselled antenatally regarding institutional delivery, encouraging trial of labour after caesarean section in select group of patients with close fetal and maternal monitoring for early detection of complications and its management reduces maternal and perinatal mortality and morbidity.